The Immunomodulatory Capacity of Induced Pluripotent Stem Cells in the Post-stroke Environment - Spellicy, Samantha E.; Hess, David C. (Frontiers in Cell and Developmental Biology, 2021)
Inflammation has proven to be a key contributing factor to the pathogenesis of ischemic and hemorrhagic stroke. This sequential and progressive response, marked by proliferation of resident immune cells and recruitment of peripheral immune populations, results in increased oxidative stress and neuronal cell death. Therapeutics aimed at quelling various stages of this post-stroke inflammatory response have shown promise recently, one of which being differentiated induced pluripotent stem cells (iPSCs). While direct repopulation of damaged tissues and enhanced neurogenesis are hypothesized to encompass some of the therapeutic potential of iPSCs, recent evidence has demonstrated a substantial paracrine effect on neuroinflammation. Specifically, investigation of iPSCs, iPSC-neural progenitor cells (iPSC-NPCs), and iPSC-neuroepithelial like stem cells (iPSC-lt-NESC) has demonstrated significant immunomodulation of proinflammatory signaling and endogenous inflammatory cell populations, such as microglia. This review aims to examine the mechanisms by which iPSCs mediate neuroinflammation in the post-stroke environment, as well as delineate avenues for further investigation.